OPTIMAL CONCENTRATION OF BASIL LEAF EXTRACT (Ocimum basilicum L.) IN INHIBITING THE GROWTH OF Streptococcus mutans IN VITRO - Syahrul, Dwis; Syahriel, Dwis (Faculty of Dentistry, Mahasaraswati Denpasar University, 2021)
Introduction: One of flora in the oral cavity is Streptococcus mutans as a cause of dental caries. Various ways can be done to suppress its growth, one of them by using mouthwash which is used contains a lot of chemicals, so an alternative is needed by using herbal ingredients, including basil (Ocimum basilicum L.) leaves that contain essential oils, methyl eugenol, phenols, and flavonoids which are able to work as antibacterial. The purpose of this study was to determine the inhibition and optimal concentration of basil leaf extract on the growth of Streptococcus mutans. Materials and method: The method used agar Kirby Bauer method with seven treatments of leaf extract with concentrations of 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, and methanol solution as control group. The culture medium used was Muller Hinton Blood Agar. Results and discussions: The Kruskall Wallis test showed a significant difference between treatment groups. Mann Whitney U-Test test, found that the control group, basil leaf extract concentrations of 1.5%, 2%, 2.5% and 3% were tested with concentrations of 3.5% and 4% had a significant difference. The test between groups of 3.5% and 4% basil leaf extract did not show a significant difference. Conclusion: this study was that in vitro basil leaf extract with a concentration of 3.5% and 4% had inhibitory power on the growth of Streptococcus mutans and basil leaf extract with a concentration of 3.5% optimally inhibited the growth of Streptococcus mutans in vitro.